Dampak varian arteri radialis pada prosedur transradial - Loretta C. Wangko; Bambang Budiono; Reggy L. Lefrandt (The Indonesian Heart Association, 2014)
Nowadays, transradial approach has become the most chosen procedure by the intervention cardiologists, either in diagnostic or coronary intervention. Possibilities of vascular variants of the radial artery and along the vascular axis until the aortic arch are not a reasonable challenge for not using this transradial approach. Complications due to the transradial approach are very rare and mostly are easier to be managed than due to the other approaches. Besides that, eary ambulation, comfortability and satisfaction of the patients, and a relative low cost lead it to be the most preferable one. Data and publication of variants along the axis of the radial artery to the aortic arch are very supporting to the procedure success. A thorough understanding and consideration about the variants can diminish the failure of this transradial approach or the crossover to another approach.